Adhesion and activation of platelets from subjects with coronary artery disease and apparently healthy individuals on biomaterials. Issue 1 (28th January 2015) - Braune, S.; Groß, M.; Walter, M.; Zhou, S.; Dietze, S.; Rutschow, S.; Lendlein, A.; Tschöpe, C.; Jung, F.
Abstract: On the basis of the clinical studies in patients with coronary artery disease (CAD) presenting an increased percentage of activated platelets, we hypothesized that hemocompatibility testing utilizing platelets from healthy individuals may result in an underestimation of the materials' thrombogenicity. Therefore, we investigated the interaction of polymer‐based biomaterials with platelets from CAD patients in comparison to platelets from apparently healthy individuals. In vitro static thrombogenicity tests revealed that adherent platelet densities and total platelet covered areas were significantly increased for the low (polydimethylsiloxane, PDMS) and medium (Collagen) thrombogenic surfaces in the CAD group compared to the healthy subjects group. The area per single platelet—indicating the spreading and activation of the platelets—was markedly increased on PDMS treated with PRP from CAD subjects. This could not be observed for collagen or polytetrafluoroethylene (PTFE). For the latter material, platelet adhesion and surface coverage did not differ between the two groups. Irrespective of the substrate, the variability of these parameters was increased for CAD patients compared to healthy subjects. This indicates a higher reactivity of platelets from CAD patients compared to the healthy individuals. Our results revealed, for the first time, that utilizing platelets from apparently healthy donors bears the risk of underestimating the thrombogenicity of polymer‐based biomaterials. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 104B: 210–217, 2016.